Screen-Printed Superconducting Y-Ba-Cu-O Thick Films on Various Substrates - T. Kokkomäki; A. Uusimäki; R. Rautioaho; J. Levoska; T. Murtoniemi; S. Leppävuori (Active and Passive Electronic Components)
Superconducting thick films of the Y-Ba-Cu-O system prepared by screen-printing and sintering on different substrates were investigated to study the effect of the substrate material on the superconducting properties of the films. These properties were determined by carrying out structural studies using SEM, EPMA and XRD and by determining the electrical resistivity. The effect of diffusion barrier layers between the film and the substrate on the superconducting properties of the film was also studied. The onset temperature of superconductivity in YBa2Cu3O7−δ (123) superconducting thick film was around 92 K on almost all the substrates. The substrate material had an influence on the temperature at which zero resistance (i.e. Tc) was attained. This varied from 85 K on yttrium stabilized zirconium oxide (YSZ) and nickel substrates down to below 70 K on other substrates. Nickel offered promise as being a good diffusion barrier between the substrate and the 123 superconducting thick film because the reactions between the film and nickel occurred slowly and did not impair the superconducting properties of the film. In the case of alumina substrates, there was a rapid reaction which took place at high annealing temperatures. A BaAl2O4 phase was found between the film and the alumina substrate which promoted adhesion but resulted in poor superconducting properties of the film.